The Role of Brand Image, Brand Experience, Influencer Marketing and Purchase Interest on Cunsumer Purchasing Decisions of Handphone - Purwanto, Agus; Zaidan Prayuda, Rafie (PROFESOR : Professional Education Studies and Operations Research, 2024)
This research was conducted with the aim of showing the influence of brand image, brand experience and influencer marketing on purchasing decisions with the purchase interest variable. This research uses a quantitative survey approach. The research population is cellphone consumers whose total is not known with certainty. Sampling used purposive sampling technique and obtained 234 samples. The data analysis technique uses path analysis with the partial least squares structural equation modeling (PLS-SEM) method with data processing tools using Smart-PLS 3.0 software. The results of this research are that Brand Image has a significant influence on Purchase Interest, Brand Experience has a positive and significant influence on Purchase Interest, Influencer Marketing has a positive and significant influence on Purchase Interest. And Purchase Interest has a significant influence on Purchase Decisions. In this study, the researcher's limitation was only using purchase intention as seen from self-congruity theory. So in future research it is recommended to look at purchasing interest from other theoretical aspects that are considered more appropriate to the type of research used